TRANSGENIC TOBACCO PLANTS WITH STRONGLY DECREASED EXPRESSION OF PYROPHOSPHATE - FRUCTOSE-6-PHOSPHATE 1-PHOSPHOTRANSFERASE DO NOT DIFFER SIGNIFICANTLY FROM WILD-TYPE IN PHOTOSYNTHATE PARTITIONING, PLANT-GROWTH OR THEIR ABILITY TO COPE WITH LIMITING PHOSPHATE, LIMITING NITROGEN AND SUBOPTIMAL TEMPERATURES - Sonnewald, Uwe; et al. (Planta, 1995)
Transformation of tobacco with the potato gene encoding the subunit of pyrophosphate: fructose-6-phosphate 1-phosphotransferase (PFP) in the antisense orientation under the control of the constitutive CaMV 35S promoter, followed by selfing and crossing of the transformants, generated a line of tobacco (5-37) with up to an 85% reduction in PFP activity in the shoot. Transformants containing a sense construct (4-40-91) contained only 1-3% of wild-type PFP, presumably due to co-suppression. Rates of photosynthesis and partitioning between sucrose and starch in source leaves were identical in 4-40-91 transformants and the wild type. In the dark in sink leaves of 4-40-91 transformants, levels of hexose phosphates were up to 50% higher, glycerate-3-phosphate 30% lower and fructose-2,6-bisphosphate threefold higher than in the wild type; inorganic pyrophosphate, pyruvate and the ATP/ADP ratio were unaltered. Low -PFP and wild-type plants did not differ significantly in their rate of growth at 25 degrees C and 200 mu mol quanta . m(-2). s(-1) on full nutrient medium. Growth on limiting phosphate and limiting nitrogen was inhibited identically in the wild type and transformants, and transformants adjusted their shoot/root ratio in an identical manner to the wild type. Differences in fructose-2,6-bisphosphate and glycolytic metabolites between the wild type and transformants were no larger in these suboptimal nutrient conditions, than in optimal conditions. Growth of the wild type and 4-40-91 transformants was inhibited identically at 12 degrees C compared to 25 degrees C. Differences in fructose-2,6-bisphosphate were smaller when the genotypes were compared at 12 degrees C than at 25 degrees C. We conclude that PFP does not play an essential role in photosynthate partitioning in source leaves. During respiratory metabolism in sink leaves it catalyzes a net glycolytic flux, as in potato tubers. However, tobacco seedlings are able to compensate for a large decrease in expression of PFP without loss of growth, or the ability to cope with suboptimal phosphate, nitrogen or temperature.
Keywords: NICOTIANA; NUTRIENT DEFICIENCY; PYROPHOSPHATE-FRUCTOSE-2-PHOSPHATE 1-PHOSPHOTRANSFERASE; RESPIRATION; TEMPERATURE; TRANSGENIC PLANT